Immunoregulatory effects of Huaier (Trametes robiniophila Murr) and relevant clinical applications - Long, Hongrong; Wu, Zhongcai (Frontiers in Immunology, 2023)
Huaier (Trametes robiniophila Murr) is a medicinal fungus of traditional Chinese medicine with more than 1000 years of history of clinical application. Its remarkable anticancer activities has led to its application in treating diverse malignancies. In recent years, the immunomodulatory effects of Huaier have been uncovered and proved to be beneficial in a plethora of immune-related diseases including cancer, nephropathy, asthma, etc. In this review, we comprehensively summarized the active components of Huaier, its regulatory activities on multifaceted aspects of the immune system, its application in various clinical settings as well as toxicologic evidence. Based on currently available literature, Huaier possesses broad-spectrum regulatory activities on various components of the innate and adaptive immune system, including macrophages, dendritic cells, natural killer cells, T and B lymphocytes, etc. Versatile immunologic reactions are under the regulation of Huaier from expression of damage-associated molecular patterns, immune cell activation and maturation to cell proliferation, differentiation, antibody production, expression of cytokines and chemokines and terminal intracellular signal transduction. Moreover, some modulatory activities of Huaier might be context-dependent, typically promoting the restoration toward normal physiological status. With excellent efficacy and minimal side effects, we foresee more extensive application of Huaier for treating immune-related disorders.